A pilot study of chest tube versus pigtail catheter drainage of acute hemothorax in swine. Issue 6 (December 2015) - Russo, Rachel M.; Zakaluzny, Scott A.; Neff, Lucas P.; Grayson, J. Kevin; Hight, Rachel A.; Galante, Joseph M.; Shatz, David V.
Abstract : BACKGROUND: Evacuation of traumatic hemothorax (HTx) is typically accomplished with large-bore (28–40 Fr) chest tubes, often resulting in patient discomfort. Management of HTx with smaller (14 Fr) pigtail catheters has not been widely adopted because of concerns about tube occlusion and blood evacuation rates. We compared pigtail catheters with chest tubes for the drainage of acute HTx in a swine model. METHODS: Six Yorkshire cross-bred swine (44–54 kg) were anesthetized, instrumented, and mechanically ventilated. A 32 Fr chest tube was placed in one randomly assigned hemithorax; a 14 Fr pigtail catheter was placed in the other. Each was connected to a chest drainage system at −20 cm H2 O suction and clamped. Over 15 minutes, 1, 500 mL of arterial blood was withdrawn via femoral artery catheters. Seven hundred fifty milliliters of the withdrawn blood was instilled into each pleural space, and fluid resuscitation with colloid was initiated. The chest drains were then unclamped. Output from each drain was measured every minute for 5 minutes and then every 5 minutes for 40 minutes. The swine were euthanized, and thoracotomies were performed to quantify the volume of blood remaining in each pleural space and to examine the position of each tube. RESULTS: Blood drainage was more rapid from the chest tube during the first 3 minutes compared with the pigtail catheter (348 ± 109 mL/min vs. 176 ± 53 mL/min), but this difference was not statistically significant ( p = 0.19). Thereafter, the rates of drainage between the two tubes were not substantially different. The chest tube drained a higher total percentage of the blood from the chest (87.3% vs. 70.3%), but this difference did not reach statistical significance ( p = 0.21). CONCLUSION: We found no statistically significant difference in the volume of blood drained by a 14 Fr pigtail catheter compared with a 32 Fr chest tube.